2015
DOI: 10.1055/s-0035-1557905
|View full text |Cite
|
Sign up to set email alerts
|

ICG Fluorescence Technique for the Detection of Sentinel Lymph Nodes in Breast Cancer: Results of a Prospective Open-label Clinical Trial

Abstract: Introduction: Detection of sentinel lymph nodes (SLN) is the standard procedure to evaluate axillary lymph node status in breast cancer. In addition to known and established procedures such as the blue dye method and scintigraphy, this study investigated the efficacy of a method based on use of the fluorescent dye indocyanine green (ICG). Patients and Method: A total of 126 women with breast cancer histologically verified by punch biopsy were studied during surgical removal of SLN. In addition to SLN marking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 31 publications
3
41
0
7
Order By: Relevance
“…Coufal et al discussed an impact of BMI on ICG detection of SLNs, which depended on world region . Our study suggests that high BMI may impact on ICG SLN detection, as previously reported by Ayoma et al and Grischke et al Ayoma et al reported that a successful lymphatic drainage pathway was mapped in patients with a mean BMI of 22.3 kg/m 2 (range, 17.9‐33 kg/m 2 ) …”
Section: Discussionsupporting
confidence: 82%
“…Coufal et al discussed an impact of BMI on ICG detection of SLNs, which depended on world region . Our study suggests that high BMI may impact on ICG SLN detection, as previously reported by Ayoma et al and Grischke et al Ayoma et al reported that a successful lymphatic drainage pathway was mapped in patients with a mean BMI of 22.3 kg/m 2 (range, 17.9‐33 kg/m 2 ) …”
Section: Discussionsupporting
confidence: 82%
“…Our assumption as to the crucial influence of depth of the detected structures on the success rate of visualization is supported also by the conclusions of several other studies. German authors have stated that body mass index (BMI) higher than 40 is a limiting factor for using ICG in breast cancer [29]. Although the highest BMI in our patient set reached only 30.9, it is apparent that deeper location of the SLNs in patients with a stronger subcutaneous layer complicates their fluorescent detection.…”
Section: Discussionmentioning
confidence: 73%
“…This is the reason why the slightly enhanced costs of the surgical procedure have been considered as irrelevant. Considering data in the Literature, showing an equivalence in sensibility and specificity between the two methods [11][12][13][14][15][16][17][18], we have analyzed the economic impact of the two clinical pathways in the management of breast cancer.…”
Section: Methodsmentioning
confidence: 99%